Oil Sector in Iraq (Reality and Prospects) Economic Analysis - صالح ربيع خلف; محمد ايهاب عباس (Journal of Economics and Administrative Sciences, 2013)
The oil sector in Iraq suffered from several difficulties led to the decline and reduction of oil production and the deterioration of refineries and transport pipeline status in addition to the weakness of the technology side and the prevalence of financial and administrative corruption besides the high costs of rehabilitation of the oil sector and also administrative and institutional problems still ongoing. In spite of Iraq’s possession of vast oil wealth allows him to play an important role in the international energy market، he is still under the level. The production of oil doesn’t suit with its enormous oil proven، most of natural gas is flaming or shrinkage، the technology which is used is still suffered of the ancient technologic، or Iraq is still works with technological of eighties this order reflex negatively on the sector Iraqi oil industry.